ANALISIS PERBANDINGAN PELAKSANAAN PENGELOLAAN PAJAK BUMI DAN BANGUNAN SEBELUM DAN SESUDAH MENJADI PAJAK DAERAH DIKABUPATEN SUKOHARJO - Usman, Fadlil; Yohandika, Victario Marthaardi (Polytechnic of State Finance STAN, 2015)
Handover of PBB P2 to local governments is based on Undang-undang Nomor 28 Tahun 2009 tentang Pajak Daerahdan Retribusi Daerah(PDRD).In its implementation,local governments need to be ready in all management aspects including the administration of the collection.This study aimed to compare the implementation of managing PBB P2 before and after becoming local taxes. The research method used is descriptive qualitative analysis. The results showed that there were no differences in theÂ implementationof PBBP2 management, in the SOP PBB P2, in PBB P2 rate and the number of villages served.